Comparison of antibacterial effect of Scrophularia Striata extract, sodium hypochlorite and chlorhexidine on Enterococcus faecalis in tooth root canals - Mohammad Fazeli; Masomeh Ahmadi; Parisa Asadollahi; Hossein Seyedkhani; Elahe Karimi; liela ghitani; Nahid Mahdian; Hossein Kazemian (Tehran University of Medical Sciences, 2023)
Background and Aims: Root canal treatment failures are often attributed to incomplete removal of bacteria, particularly Enterococcus faecalis. While, chlorhexidine and sodium hypochlorite serve as conventional treatments. herbal medicine has been today considered as an alternative to synthetic medicine due to its safety. Therefore, the aim of the present study was to compare the antibactrial effect of Scrophularia Striata extract with chlorhexidine and sodium hypochlorite on Enterococcus Faecalis in the tooth root canal. Materials and Methods: In this study, sixty extracted teeth were examined. Following the infection of dental canals with Enterococcus faecalis, materials were tested in 3 groups: 1) chlorhexidine 2% (18 teeth), 2) sodium hypochlorite 2.5% (18 teeth), and 3) Scrophularia striata (at the concentration obtained from MIC, 20%; 18 teeth). Additionally, the positive control and negative control were included (3 teeth in each group). Samples were then cultured on bile esculin agar. After 72 hours, black colonies were eaxamined. Chi-squared test was used to analyze the results. Results: Enterococcus faecalis bacteria grew in 6, 8, and 17 out of the 18 teeth within the sodium hypochlorite, chlorhexidine, and Scrophularia striata extract groups, respectively. Consequently, the bactericidal effects for sodium hypochlorite, chlorhexidine, and Scrophularia striata extract were 66.6%, 55.5%, and 5.55%, respectively. Conclusion: The antibacterial effect of the Scrophularia striata extract was significantly lower than chlorhexidine and sodium hypochlorite on Enterococcus faecalis in dental canals viewed as a suitable replacement to the already in use synthetic therapeutic irrigants.